2011
DOI: 10.1111/j.1365-2672.2011.05104.x
|View full text |Cite
|
Sign up to set email alerts
|

Alkane-degrading properties of Dietzia sp. H0B, a key player in the Prestige oil spill biodegradation (NW Spain)

Abstract: Aims:  Investigation of the alkane‐degrading properties of Dietzia sp. H0B, one of the isolated Corynebacterineae strains that became dominant after the Prestige oil spill. Methods and Results:  Using molecular and chemical analyses, the alkane‐degrading properties of strain Dietzia sp. H0B were analysed. This Grampositive isolate was able to grow on n‐alkanes ranging from C12 to C38 and branched alkanes (pristane and phytane). 8‐Hexadecene was detected as an intermediate of hexadecane degradation by Dietzia H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 53 publications
(120 reference statements)
0
18
1
Order By: Relevance
“…This interesting result may be explained that the CYP153 gene likely play the predominant role in alkane degradation by Dietzia sp. CN-3, which is particularly different from previous reports (Alonso-Gutierrez et al, 2011). For example, real-time qPCR analysis showed that alkB and CYP153 expression was significantly induced by C 14 , C 16 and pristane, and the transcript levels of the two genes were all >20-fold induced in Dietzia maris As-13-3 .…”
Section: Detection Of Alkane Degradation Genescontrasting
confidence: 86%
See 1 more Smart Citation
“…This interesting result may be explained that the CYP153 gene likely play the predominant role in alkane degradation by Dietzia sp. CN-3, which is particularly different from previous reports (Alonso-Gutierrez et al, 2011). For example, real-time qPCR analysis showed that alkB and CYP153 expression was significantly induced by C 14 , C 16 and pristane, and the transcript levels of the two genes were all >20-fold induced in Dietzia maris As-13-3 .…”
Section: Detection Of Alkane Degradation Genescontrasting
confidence: 86%
“…However, oil spills, as a result of natural or anthropogenic factors, cause dramatic environmental and human health problems (Head et al, 2006;Li et al, 2012). Crude oil is a complex mixture of compounds that can be classified into four main groups: saturated hydrocarbons, aromatic hydrocarbons, resins and asphaltenes (Alonso-Gutierrez et al, 2011). The search for methods to reduce petroleum pollution is becoming increasingly significant and necessary (Ouyang et al, 2005;Mbadinga et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Members of Dietzia isolated from other oil-contaminated areas have been shown to degrade hydrocarbons (Alonso-Gutiérrez et al 2011;Bødtker et al 2009;Plakunov et al 2008;von der Weid et al 2007;Wang et al 2011a). Interestingly, Dietzia psychralcaliphila sp.…”
Section: Occurrence Of Known Oil-degrading Bacteriamentioning
confidence: 97%
“…This approach makes use of indigenous oil consuming microorganisms (Ahmad et al, 2015). However, some isolated microorganisms can effectively degrade single pollutant in laboratory conditions but when introduced into actual field conditions with multiple pollutants they cease to function as anticipated, hence, the need for bioaugmentation (Alonso-Gutierrez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%